(untitled) (Experimental biology, 2022)
Establishing precise gene expression patterns in different cell types is essential for the proper differentiation and development of multicellular organisms. The resulting level of transcription is determined both by the genetic nucleotide sequence of DNA and by epigenetic factors that modify chromatin. Epigenetic repressors of the Polycomb group (PcG) are regulatory proteins that repress gene transcription and maintain correct pattern of gene expression in multicellular organisms. PcG proteins form two main complexes: Polycomb Repressive Complex 1 (PRC1) and Polycomb Repressive Complex 2 (PRC2) that possess ubiquitin ligase and histone methyltransferase enzymatic activities, respectively. Several mechanisms have been suggested to account for the recruitment of Polycomb proteins in mammals, one of which involves interactions with specific DNA-binding factors. While deregulation main PcG genes in cancer have been well documented, the role of PcG DNA-binding partners in oncology remains elusive. In the present study, we analyzed genomic and transcriptomic databases of clinical tumor samples (cBioPortal, TNMplot, KMplot) to evaluate clinical correlations of Polycomb-associated DNA-binding proteins. We found that amplifications and higher expression of the ZNF281 gene are often found in pancreatic cancer and correlate with poor prognosis of overall survival.